Determination of Total Folates in Complex Nutritional Drinks and Supplements Using a Tri-Enzyme Microbiological Method and Michaelis-Menten Kinetics. (23rd November 2019) - Kobany, Stephanie; Schmieg, Dana; Plank, David W; Povolny, Lisa A; Shepard, Marilyn; Lam, May; Galvan, Noe; Brown, Dana
Abstract: Background: Recent development of LC methods for the determination of total folates (vitamin B9) in complex matrixes have been hindered by vitamer interconversion and yield variability. The official microbiological method (AOAC Official Methods of Analysis 944.12 and 960.46) uses an end point turbidity reading to determine folate concentration. However, when measuring complex matrixes, shifts are observed in the growth curves of the microorganism and inaccuracies are introduced to this quantification method. Objective/Methods: In addition to the tri-enzyme digestion of the standard microbiological method, we have applied enzyme modeling of the initial velocity of bacterial growth using Michaelis-Menten kinetics to achieve more accurate and reproducible determinations of total folates. Results/Conclusions: Accuracy determined through spike recovery in Infant/Adult Nutritional Drink and a complex vitamin matrix gave values acceptable to AOAC standards of 85–110%. Repeatability of the low mass fraction analyte measured at micrograms per 100 g yielded relative standard deviations <15% for all matrixes tested, including three standard reference materials.